Outcome of surgical management of the thoracic outlet compression syndrome in a district general hospital. - Baker, D. M. (Royal College of Surgeons of England, 1993)
The 5-year experience of one surgeon in treating 50 consecutive patients (57 limbs) with the thoracic outlet compression syndrome (TOCS) is described. A predominance of neurological symptoms presented; each was treated in a similar fashion with extensive resection of the first rib and excision of fibrous bands and cervical ribs. Results of surgery (84% complete resolution or improvement of symptoms) compare favourably with others. This series demonstrates that although the technicality of the surgery demands a surgeon very familiar with the operation, this need not be undertaken in a regional centre.